Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Snowball Throwing di Sekolah Dasar - Mawaddah Warahmah; Atri Waldi (Universitas Negeri Padang, 2023)
This research is motivated by the learning outcomes of students who are still low. The aim of the study is to describe the increase in student learning outcomes in integrated thematic learning using the Snowball Throwing Cooperative Model in Class V SD Negeri 37 Sungai Bangek Kota Padang. This type of research is Classroom Action Research using a qualitative approaches and quantitative approaches carried out in two cycles, with three meetings consisting of four stages, namely planning, implementation, observation and reflection. Data collection techniques are in the form of observation, test and non-test analysis. The research subjects were class teachers, researchers and students totaling 24 people. The results of research on lesson plans in cycle 1 obtained an average of 83.33% (B) and increased in cycle 2 to 94.44% (SB), cycle 1 teacher activities obtained an average of 86.11% (B) and increased in cycle 2 to 94.44% (SB), student activities in cycle 1 obtained an average of 84.72% (B) increased in cycle 2 to 91.67% (SB), and student learning outcomes in cycle 1 obtained an average of 71.46 (B) and increased in cycle 2 to 87.14 (A). Thus, the Snowball Throwing cooperative model can improve student learning outcomes in integrated thematic learning in class V SD Negeri 37 Sungai Bangek Kota Padang.